RE-DESAIN SISTEM JARINGAN PIPA AIR BERSIH DUSUN KATAPANG DESA LOKKI KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT - Samallo, Elsina Juliana; Warniyati, Warniyati; Tutkey, Monica Rina; Sihombing, Tri Octaviani (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
The availability of clean water is a fundamental need that is crucial for the survival of all living beings, including humans. Katapang Hamlet, located in Lokki Village, Huamual District, West Seram Regency, faces serious issues related to the distribution of clean water due to frequent pipeline system failures, particularly caused by flooding. The pipeline system in this area has been built three times, but it continues to experience damage, affecting the clean water distribution to the community. The current system is highly vulnerable to natural disasters such as floods, with pipelines located in high-risk areas like riverbanks and steep cliffs, irregular pipeline routes, and inadequate system components. During floods, the community often goes without a clean water supply for days. To address this problem, a redesign of the clean water distribution network is required. This study aims to design an optimal clean water distribution system using Epanet 2.2 software. Through this application, the analysis and simulation of the distribution pipeline network are carried out to ensure that the system continues to function well, even during heavy rain or floods, so that the community can consistently receive a clean water supply. The results of this study are expected to provide a long-term solution to the clean water distribution problems in Katapang Hamlet.